2011
DOI: 10.1093/eurpub/ckr143
|View full text |Cite
|
Sign up to set email alerts
|

Mortality amenable to health care and its relation to socio-economic status in Hungary, 2004–08

Abstract: Differences in deprivation alone cannot explain the spatial distribution of mortality amenable to health care. This study highlights the importance of exploring other factors (e.g. health-care system and individual life style) beyond socio-economic status, which affect health inequalities particularly for health policy makers, who are responsible for the mitigation of health disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…Up to now, there are some studies that assessed the regional differences in amenable mortality, e.g. for Italy (28), for Spain (29), for Hungary (30), etc. This seems to be the subject of our further analyses in the field of amenable mortality studies.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, there are some studies that assessed the regional differences in amenable mortality, e.g. for Italy (28), for Spain (29), for Hungary (30), etc. This seems to be the subject of our further analyses in the field of amenable mortality studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Tobias and Yeh found that amenable causes make an important contribution to the mortality differentials between socio-economic groups in New Zealand, with data from 1981–84 and 2001–04 [8]. Furthermore, Nagy, et al, examining data from 2004 to 2008, found a relationship between the risks of death due to amenable causes and deprivation in geographical areas of Hungary [22]. Schoenbaum, et al provided evidence of excessive amenable mortality in areas with higher populations of poor and black people in the US in 2005 [21].…”
Section: Discussionmentioning
confidence: 99%
“…A possible interpretation of this finding is that SDR is influenced by organizational and care delivery models and different priority settings—not by the amount of dedicated resources. Recently, Nagy et al [28] also reported a positive association between amenable mortality and deprivation status in both genders.…”
Section: Discussionmentioning
confidence: 99%